Nguiu Aboriginal community (Bathurst Island, Tiwi Island) report : 21 July 1997 to 5 December 1997 - Thorne, Ken; Butler, Veronica; Northern Territory Living with Alcohol Program (Territory Health Services, 2017)
The Aboriginal Family Violence Strategy (AFVS) is an interactive process or an 'open framework' approach, where Aboriginal community people share responsibility for the design and development of their own programs and take 'action' in their communities. Y